Influencers, Gold Price Perception, and Behavioral Moderators in Retail Stock Investment Interest - Metha Dwi Apriyanti; Hendra Galuh Febrianto; Amalia Indah Fitriana; Andry Priharta; Mikail Kartaloğlu (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study investigates how stock market influencers and gold price perception shape retail investors’ investment interest, with digital engagement and risk tolerance as moderators. Research Design & Methods: A survey of 300 Indonesian retail investors was conducted using purposive sampling. Data were analyzed through SEM-PLS, including validity and reliability tests. Findings: Influencers significantly increase investment interest, whereas perceptions of the gold price reduce it. Digital engagement strengthens both the positive effect of influencers and the negative effect of gold perception. Risk tolerance weakens influencer effects but mitigates the adverse impact of gold perception. The influencer interest path shows the strongest coefficient. The model explains 63% of the variance in investment interest and has strong predictive relevance. Implications & Recommendations: Practitioners should leverage digital strategies and influencer collaborations while addressing concerns about the gold price through financial education. Policymakers may design risk-based literacy programs to balance enthusiasm for digital technologies with safe investment behavior. Contribution & Value Added: This study integrates dual moderating roles of digital engagement and risk tolerance, offering a novel framework to understand retail investor behavior in emerging markets amid digitalization and social media influence.